FEATURES OF IMMUNOREACTIVITY CHILDREN WITH ALLERGIC DISEASES IN DIFFERENT AREAS OF THE JIZZAKH REGION OF Ruz (American Journal of Interdisciplinary Research and Development, 2024)
An immunological examination was carried out on 110 children aged 7 to 14 years with AR, BA, AD, living in 3 districts of the Jizzakh region. The data obtained on the nature of immunological disorders in children with allergic diseases make it possible to determine the characteristics of the impact of climatic, environmental and industrial factors on the immune system.